Producing globalisation : Politics of discourse and institutions in Greece and Ireland. - Antoniades, Andreas (Manchester University Press, 2010)
How can we study globalisation in a way that transcends the material/ideational rift? How has globalisation resonated and/or dominated in different national contexts? What role has been played by national political economies and domestic institutions in this process?*Producing globalisation* attempts to scrutinise the nature of the interplay between globalisation and national institutional settings. Rather than taking globalisation as a given, this book explores how concrete political actors produced the phenomenon of globalisation. Such an approach aims to bring human agency and its importanc.